PEMBUATAN BAKSO SEHAT DENGAN PENAMBAHAN BUAH NAGA MERAH BAGI MASYARAKAT DI DESA SRIKATON, KECAMATAN PONDOK KELAPA, BENGKULU TENGAH - Suharyanto Suharyanto; Edi Soetrisno; Y Yurike (UNIB Press, 2021)
Meatballs are meat-based processed products that are favored by most people. This is very positive because it can be a medium for increasing the consumption of animal protein from meat for the community. However, the popularity of this meatball must be balanced with its availability in a healthy formula for consumers. Problems that occur in Srikaton Village, including 1) The low awareness of the community to produce and consume healthy natural processed products; 2) Public awareness is still low in the consumption of protein derived from meat; 3) In the midst of the Covid-19 pandemic, the people of Srikaton Village need to increase their family business to increase family income. Based on the problems above, the solution offered is to provide training for making healthy meatballs with the addition of red dragon fruit. The purpose of this activity is to introduce the benefits of the importance of consuming animal protein and to utilize red dragon fruit in making meatballs to increase antioxidants, become very attractive preservatives and natural dyes. Besides that, it can also increase people's income because basically it can be done with a home industry scale and become a business for people who live in rural areas. Activities are carried out using the method of material presentation, discussion and practice. The result of this community service is increasing public awareness in producing and consuming healthy natural processed products and the creation of meatball products with a nutritious mixture of dragon fruit. There is a need for the sustainability of this activity, especially the existence of innovation training or diversification of other food products. Keywords: Healthy meatballs; Red dragon fruit; Diversification; Innovation